PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS DISCOVERY LEARNING UNTUK MATERI ARITMATIKA SOSIAL SMP/MTs - Nurul Faizah; Yenita Roza; Kartini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the limited learning instrument of mathematic as a mean of supporting learning on the Curiculum 2013. This research aims to develop the mathematics learning instruments which includes Lesson Plan (LP) and Student Worksheet (SW) based on discovery learning of arithmetic for Junior High School. The development research procedure is carried out with reference to the 4-D model developed by Thiagarajan. This research is done through the stage of define to develop due to limitation on the researcher. Learning instrument that have been developed and then validated by four validators consisting of two lectures of mathematics education and two mathematics teacher. Learning instrument have been validated and then revised based on the suggestion of the validators. Researcher did two tested that are small group tested and large group tested. Researcher did the small scale experiment for 10 students of SMPN. 13 Pekanbaru to determine the validity level of six SW. Researcher also did the large group tested to 38 students of VII.10 SMPN 13 Pekanbaru to applying the LP and SW and getting the respond from students. Based on data analys of validation and respsond from students it can be conclude in form of LP for social arithmetic is valid with percentage of average is 91.97% and learning instruments in form of SW is very valid with percentage of average is 89.40%. Based on the result of small scale experiment to six SW be obtained that the six SW had been developed already qualified practicality with percentage is 94.17%. Result of large scale experiment for SW-1 is 95.70% and to sufficient of practicality criterion.Key word : Reseach of Development, Lesson Plan (LP), Student Worksheet (SW), Discovery Learning.